Antibacterial Activity and Toxicity Profiles of Epilobium parviflorum (Schreb.) Schreb. Extracts and Conventional Antibiotics against Bacterial Triggers of Some Autoimmune Diseases - Batten, Jason; Cock, Ian E (Pharmacognosy Communications)
Background: Epilobium parviflorum (Schreb.) Schreb. has been used traditionally to treat prostate, bladder and kidney diseases, as well as inflammation. However, E. parviflorum extracts are yet to be tested for the ability to inhibit the growth of bacterial triggers of autoimmune diseases. Materials and Methods: Antimicrobial activity was assessed using disc diffusion and liquid dilution minimum inhibitory concentration (MIC) assays against a panel of bacterial triggers of some autoimmune diseases. Interactions between the E. parviflorum extracts and conventional antibiotics were studied and classified using the sum of the fractional inhibitory concentration (∑FIC). Notable synergistic interactions were further examined across a range of ratios using isobologram analysis. The toxicity of the individual samples and the combinations was assessed using the Artemia lethality assay (ALA) assay. Results: Epilobium parviflorum extracts displayed notable antibacterial activity against the bacterial trigger of rheumatoid arthritis (P. mirabilis), but were ineffective against K. pneumoniae, A. baylyi, P. aeruginosa and S. pyogenes. The methanolic and ethyl acetate extracts were particularly good inhibitors of P. mirabilis growth, with MIC values of 484 and 623µg/mL recorded respectively. Furthermore, combining the extracts with conventional antibiotics resulted in significant potentiation of the inhibitory activity for some combinations. Interestingly, all combinations containing chloramphenicol or ciprofloxacin produced either synergistic or additive effects against P. mirabilis. None of the individual components (nor the combinations) were toxic in the ALA assay. Conclusion: The E. parviflorum methanolic and ethyl acetate extracts displayed clinically relevant antibacterial activity against P. mirabilis when tested alone. Furthermore, the methanolic and aqueous extracts potentiated the activity of chloramphenicol and ciprofloxacin in combination. The lack of toxicity of the extract and combinations indicates that E. parviflorum methanolic and aqueous extract and antibiotic combinations may provide leads in the development of new therapies to prevent and treat rheumatoid arthritis.
Keywords: Medicinal plants; Rheumatoid arthritis; Ankylosing spondylitis; Multiple sclerosis; Conventional antimicrobials; Synergy; Drug interaction; Toxicity